The Development and Implementation of Airflow Visualization Studies ("Smoke" Studies) as a Training Tool in Aseptic Hospital Compounding Facilities - Paula E. Borgonje; Lisa Wibier; Patrick Noordman; Herman J. Woerdenbag; Bahez Gareb (MDPI AG, 2022)
In the compounding facilities of hospital pharmacies, extemporaneous preparations for parenteral administration are produced using aseptic handling. The designated environment for this practice is a clean area, such as a laminar airflow (LAF) cabinet placed in a classified cleanroom complying with good manufacturing practices (GMP) and International Organization for Standardization (ISO) 14644-1 guidelines. The European GMP Annex 1 (Revision 2020) and United States Pharmacopeia (USP) <797> monograph state that airflow visualization studies ("smoke" studies) should be performed to substantiate the cleanroom and LAF cabinet performance and their qualification status. Even though smoke studies are required by these guidelines, current literature does not describe detailed practical protocols and acceptance criteria. The objective of this study was to develop and implement a practical smoke study protocol to ensure compliance with aseptic handling guidelines in hospital pharmacies. First, a literature search was performed to collect information about smoke study protocols and acceptance criteria. Subsequently, a smoke study protocol was developed for a downflow and crossflow LAF cabinet as well as for grade C/B cleanroom areas. As a proof of concept, the smoke study protocol for the downflow LAF cabinet was executed in the at-rest and in-operation states. Video recordings of the smoke studies were analyzed to assess the performance of the cabinet. Finally, the video recordings obtained from the smoke studies were used in a training program for hospital pharmacy operators, which showed that smoke studies might aid in operators' aseptic handling awareness. To the best of our knowledge, the present study provides for the first time a practical approach for the development of smoke study protocols in a hospital pharmacy setting and shows potential for training operators, process optimization, and continuous quality improvement.